2013
DOI: 10.1590/s0034-737x2013000600006
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate leaching through climatologic water balance in a fertigated coffee plantation

Abstract: RESUMO Lixiviação de nitrato por meio do balanço hídrico climatológico na cultura de café fertirrigadaAs perdas de nitrato no perfil do solo por lixiviação devem ser monitoradas preferencialmente em ocasiões de altas precipitações pluviométricas e irrigações quando o uso de insumos nitrogenados é elevado. Foi utilizado o balanço hídrico climatológico empregando os modelos de Thornthwaite e Penman Monteith na obtenção da estimativa de evapotranspiração potencial para calcular os fluxos de drenagem de água abaix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…However, the role that nitrogen leaching plays in agricultural Cerrado is inconclusive. In the eastern Cerrado, Bortolotto et al (2012Bortolotto et al ( , 2013 reported extremely high N-applications during fertigation (irrigation combined with fertilizer application) in coffee plantations at a rate of up to 800 kg N ha À1 a À1 . Most commonly, nitrogen fertilizer (for cotton up to 180 kg ha À1 N and maize~90 kg ha À1 ) is applied as urea with 1/3 of the total N rate during the seeding stage of the second crop (usually maize or cotton) after the soybean harvest.…”
Section: Discussion Of the Combined Effects Of Water And Land Degradamentioning
confidence: 99%
See 1 more Smart Citation
“…However, the role that nitrogen leaching plays in agricultural Cerrado is inconclusive. In the eastern Cerrado, Bortolotto et al (2012Bortolotto et al ( , 2013 reported extremely high N-applications during fertigation (irrigation combined with fertilizer application) in coffee plantations at a rate of up to 800 kg N ha À1 a À1 . Most commonly, nitrogen fertilizer (for cotton up to 180 kg ha À1 N and maize~90 kg ha À1 ) is applied as urea with 1/3 of the total N rate during the seeding stage of the second crop (usually maize or cotton) after the soybean harvest.…”
Section: Discussion Of the Combined Effects Of Water And Land Degradamentioning
confidence: 99%
“…Gücker et al (2009) provided evidence for nitrate leaching, that is, significantly high levels, in groundwater samples influenced by agriculture. In the eastern Cerrado, Bortolotto et al (2012Bortolotto et al ( , 2013 reported extremely high N-applications during fertigation (irrigation combined with fertilizer application) in coffee plantations at a rate of up to 800 kg N ha À1 a À1 . In field experiments, they confirmed that nitrate leaching and groundwater pollution would occur.…”
Section: Discussion Of the Combined Effects Of Water And Land Degradamentioning
confidence: 99%
“…Therefore, a correct management of water and fertilizers is necessary to avoid increases in production costs and minimize damages to the environment. Among the problems that arise from an excessive application of fertilizers, we can mention contamination of water tables, by which elements are leached to depths below the root system, and may reach water sources and pollute the environment (BORTOLOTTO et al 2013). Among the fertilizers that may cause pollution as a consequence of an inadequate management, we can highlight N fertilizers, with an emphasis on the nitrate ion (NO 3 -) and its action in the contamination of groundwater (ANDRADE et al, 2016), and potassium fertilizers, which may raise the levels of K + in the soil to levels above those required for crops when applied excessively (SILVA et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Os empreendimentos agrícolas têm utilizado doses cada vez mais elevadas de fertilizantes e pesticidas com o intuito de propiciar condições ótimas para o desenvolvimento das culturas e, assim, elevar as produtividades. Essas aplicações podem representar riscos ambientais às áreas cultivadas, já que pode haver contaminação do lençol freático (BORTOLOTTO et al, 2013).…”
Section: Introductionunclassified